Resistive switching behavior and mechanism in flexible TiO2@Cf memristor crossbars. Issue 8 (1st June 2019) - Hu, Simin; Yue, Jianling; Jiang, Chao; Tang, Xiuzhi; Huang, Xiaozhong; Du, Zuojuan; Wang, Chunqi
Abstract: Fiber-based memristors are expected to be one of the most ideal candidates to the future wearable nonvolatile devices. In this work, Carbon fibers coated with rutile TiO2 nanorods (TiO2 NRs) were prepared via hydrothermal method, which were denoted as TiO2 @Cf . Flexible TiO2 @Cf memristor crossbar was facilely assembled on a polyimide (PI) film. This device exhibited bi-directional threshold switching behavior and a maximum ON/OFF ratio of 10 5 . In addition, the conductance of the memristors can be continuously adjusted by consecutive sweep cycles of bias voltages. The devices also exhibit excellent endurance over 1500 cycles with a negligible shift. The carriers transport and resistance switching of the TiO2 @Cf memristor crossbar were explained by the Fowler-Nordheim tunneling model. The oxygen vacancies (OV ) in TiO2 drifted to the interface of TiO2 /Cf by an applied electric field, thereby reducing the depletion region and enhancing the current. This work provides a profound understanding of the resistive switching behavior and the related mechanism in flexible TiO2 @Cf memristor crossbars, and paves a new way for potential applications for memristors in artificial synapses and flexible devices.